Inorganic farming practices could have negative impact on environmental degradation due to excessive usage of chemical fertilizers and pesticides. One of many efforts to re-establish land productivity and reduce environmental degradation is by way of practising organic farming. The objective of this study is to explore and develop organic farming micro enterprise system supported by micro finance institution and its implication on relevant policies. The methods used in this study include soft - Bambang S. Kusmuljono; Eriyatno .; Bunasor Sanim; Gunawan Sumodiningrat (Forum Pasca Sarjana, 2007)
Inorganic farming practices could have negative impact on environmental degradation due to excessive usage of chemical fertilizers and pesticides.  One of many efforts to re-establish land productivity and reduce environmental degradation is by way of practising organic farming.  The objective of this study is to explore and develop organic farming micro enterprise system supported by micro finance institution and its implication on relevant policies.  The methods used in this study include soft system methodology approach utilizing total system intervention (TSI) mechanism that covers the principles of complementarism, social awareness and emancipation, and commitment to human well-being in the context of poverty alleviation.  The techniques being adopted include business feasibility, comparative performance index, strategic asumption surfacing test and analytical hierarchy process.  Case study was conducted in Garut regency, West Java.  The performance of organic farming activity in Garut regency is considered adequate while the most preferable micro finance institution supporting agricultural sector is the saving and loan unit from cooperative organization, but on the other hand the micro banking sector has not been attracted in general to extend credit financing to agricultural sector due mainly to risk factor.  Eventually this study has been able to introduce a concept of empowering micro enterprise in organic farming involving credit guarantee institution, technical assistance and production of organic fertilizers and pesticides. In view of enhancing the financing of organic farming, the concept of credit for microenterprise in organic farming is introduced for further development and implementation.  Furthermore the policy implication of this study is iniciatives for poverty reduction trust fund and coordinating institution for micro financing institutions and the relevant law governing micro credit and micro finance institutions.   Key words: organic farming, fertilizer, pesticide, micro enterprise, micro credit, micro finance institution